2011
DOI: 10.1007/s00774-011-0300-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and risk factors of vertebral fractures in Korea

Abstract: We investigated the prevalence and risk factors of vertebral fractures in Korea. In a community-based prospective epidemiology study, 1,155 men and 1,529 women (mean age 59 years, range 43-74) were recruited from Ansung, a rural Korean community. Prevalent vertebral fractures were identified on the lateral spinal radiographs at T11 to L4 using vertebral morphometry. Bone mineral density (BMD) was measured at the lumbar spine, femur neck and total hip. Of the 2,684 subjects, 137 (11.9%) men and 227 (14.8%) wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 42 publications
4
35
0
3
Order By: Relevance
“…Table 4 shows the age-specific SPR for morphometric VFs in AS patients compared with the morphometric VFs expected in the Korean general population [16]. There was a significant increase in the risk of morphometric VFs among AS patients aged over 40 years (standardized Prevalence rate (SPR) = 3.3, 95% CI = 2.06 to 4.54).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 4 shows the age-specific SPR for morphometric VFs in AS patients compared with the morphometric VFs expected in the Korean general population [16]. There was a significant increase in the risk of morphometric VFs among AS patients aged over 40 years (standardized Prevalence rate (SPR) = 3.3, 95% CI = 2.06 to 4.54).…”
Section: Resultsmentioning
confidence: 99%
“…When comparing the prevalence of radiographic morphometric VFs in AS patients with that in the Korean general population [16], all AS patients under 40 years of age were excluded because all members of the general population group were ≥40 years old. We applied the age-specific prevalence of morphometric VF in the Korean general population study to the age distribution of our AS cohort, and calculated an age-standardized prevalence ratio (SPR) and its 95% CI.…”
Section: Methodsmentioning
confidence: 99%
“…Vertebral fracture is one of the most common osteoporotic fractures; it is a major public health problem that affects millions of people worldwide [23]. In the Korean population, the standardized prevalence for vertebral fractures using the age distribution has been reported to be 12.6% in women and 8.8% in men [4]. …”
Section: Introductionmentioning
confidence: 99%
“…(21) However, the majority of studies have found lower mean BMI in vertebral fracture cases or no independent association with BMI for vertebral fracture. (22)(23)(24)(25)(26) The subclinical nature of most vertebral fractures and the difficulty of accurately measuring thoracic spine BMD by dual-energy X-ray absorptiometry (DXA) present particular challenges to the evaluation of adiposity and obesity on vertebral BMD and fracture risk.…”
Section: Introductionmentioning
confidence: 99%